Deafening Echoes: Lived Experiences of Adult Survivors of Online Sexual Abuse and Exploitation of Children - Dulawan, Adesty; Bance, Lucila (Asean Social Work Journal, 2024)
Online Sexual Abuse and Exploitation of Children (OSAEC) is a global phenomenon of technology-facilitated sexual violence that has become prevalent in the Philippines. This exploratory qualitative study aimed to establish an in-depth understanding of the enduring effect of OSAEC victimization and utilize the phenomenological perspectives to identify key components of a trauma intervention for the population. Specifically, in-depth interviews were held with 5 adult survivors who were initially screened for trauma and 5 psychologists who are providing therapy to survivors of sexual violence. The themes showed that adult survivors of OSAEC face instability across various aspects of their life, including financial constraints, complex family relationships, huge family responsibilities, and health issues. Furthermore, they manifest persistent trauma symptoms such as hounding fears, intrusive memories, avoidance behaviors, negative affect and cognitions. Feelings of shame and stigma related to their past experiences likewise contribute to social isolation and emotional distress. Despite these challenges, the survivors demonstrate resilience through supportive relationships and faith-based coping. Facilitating the recovery of the survivors necessitate an integrative and survivor-focused therapeutic intervention that addresses the digital aspects of the abuse; builds skills in coping and emotional regulation; and fosters resilience. At the family and community level, empowerment is needed through advocacy and education to enable them to provide support and healthy environment for survivors to thrive. The recovery programs must likewise be anchored on responsive institutional systems around the survivors.